Trends and Health Risk of Trace Metals in Fishes in Liaodong Bay, China, From 2015 to 2020 - Wang, Sujing; Zheng, Na; Sun, Siyu; An, Qirui; Li, Pengyang; Li, Xiaoqian; Li, Zimeng; Zhang, Wenhui (Frontiers in Marine Science, 2022)
Due to their toxicity, non-biodegradability, and biological amplification in the food chain, heavy metal accumulation in humans via consumption of fish has become a problem. In this study, we analyzed the concentrations of six trace metals (Cd, Cr, Cu, Ni, Pb, Zn) in 12 marine fish species collected from Liaodong Bay, China, from 2015 to 2020, so as to understand the pollution status of the bay and evaluate the impact of fish consumption on human health. In addition, 5 fish species with the potential to serve as bioindicators of metal contamination were identified for use in Liaodong Bay. In general, the average concentrations were Zn > Pb ≈ Cr > Ni ≈ Cu > Cd. There were significant differences in the concentrations in muscle tissues of fish with different feeding strategies. Total target hazard quotient values of some fish were greater than 1 in 2015 and 2016, suggesting that people were susceptible to great health risk. The year 2017 had the lowest such value, which suggests that metal pollution in Liaodong Bay was decreasing at that point. However, the monitoring of metal concentrations in marine fish from Liaodong Bay should continue to be strengthened.